KAJIAN PRAGMATIK PENGGUNAAN BENTUK PERTANYAAN DALAM ALQURAN TERJEMAHAN DEPARTEMEN AGAMA - Siti Annijat Maimunah (El-QUDWAH, 2010)
The holy quran is a means for interaction between god and His ”man”?, it uses Arabic and many question sentences. in the study of pragmatics, especially speech acts. Question sentences can be used for other meanings according to its context. The general objective of this research is to discuss the use of question sentences in the translation of holy quran. This includes qualitative and content analysis research. Here research procedures used by the researcher: observasion, sampling, recording, data reduction, making inference, doing analysis, and validation. To gain the correct analysis result, the researcher uses correction technique adapted from Lincoln and Guba. The result shows that the forms of question sentences in the Holy Quran translation can be divided into two parts, that are who-questions and yes-no questions. Who-questions are marked by pronoun without –kah (apa, mengapa, bagaimana, siapa, dari mana, and betapa) and pronoun with –kah (apakah, bagaimanakah, siapakah, mengapakah, bilakah, kapankah, manakah, di manakah, and berapakah). Meanwhile, yes-no questions are marked by question words and –kah. The functions of –kah are predicate and adverb. –kah as predicate is founded noun, verb, welsh form, adjectiv, while –kah as adverb is founded in modifiers. The researcher suggests to the teachers to give more attention to the question words either in source language or target language since they have different meaning. The teachers hoped to give explanation about their differences. This research is very strict, so that, further research to complete this study is advised.